(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This thesis explores the essence of Customer Relationship Management (CRM) systems and their alignment with modern development theories to enhance business operations and customer engagement. CRM systems have emerged as a cornerstone of strategic business practices, facilitating the collection, analysis, and utilization of customer data to foster loyalty and drive growth. The study investigates the evolution of CRM technologies, their integration into organizational frameworks, and their influence on decision-making and customer satisfaction. Drawing upon theoretical models, including systems theory, relationship marketing, and innovation diffusion, the research examines the dynamic interplay between technology, strategy, and human interaction. By synthesizing academic literature, case studies, and industry practices, the thesis provides a comprehensive understanding of CRM’s transformative role in shaping sustainable business relationships and outlines future trends and challenges. The findings aim to offer actionable insights for practitioners and contribute to the academic discourse on technology-driven relationship management.